Biofortified staples may hold the key to India’s rural malnutrition - Verma, Smriti; Kumar, Anjani (2019)
The National elections in India may well be over, but the persistent issue of malnutrition still holds the nation in its tight grip. And yet, of the myriads of topical issues that comprised political propaganda, including caste, religion, employment, farmer upliftment, and even social transfers, none of the political parties raised this critical issue. The twin problems of malnutrition and nutritional insecurity are particularly severe in rural India.